LAPAROSCOPIC APPENDECTOMY IN PEDIATRIC POPULATION: A SINGLE CENTER EXPERIENCE - Rahman, Fayaz Ur; Rahman, Zia Ur; Akhtar, Waheed; Rahman, Inayat Ur; Imran, Mohammad (Journal of Postgraduate Medical Institute, 2018)
Objective: To share our institutional experience and outcome of appendecto- my in the pediatric population early in our transition from open approach to laparoscopic. Methodology: This retrospective study was conducted in the Pediatric Surgery Unit of Khyber Teaching Hospital, Peshawar, from January 2015 to July 2017. We reviewed records of 233 patients, who underwent appendectomy. All cases were classified into early stage (ES) and complicated appendicitis (CA) on oper- ative findings. Outcome variable includes operative time, length of hospital stay (LOHS), analgesia requirement, parent/care-giver satisfaction and postopera- tive complications. Clinical and demographic data were collected and analyzed with SPSS 20. Results: A total of 98 patients were operated by laparoscopic appendectomy (LA) and 135 by open appendectomy (OA). The operative time for LA was high- er than OA both for early stage (LA 35.5 ±1.78 min, OA 33.5 ±1.68 min, p =0.53) and complicated appendicitis (LA 55 ±1.32 min, OA 40.6 ±2.05 min, p =0.005). Hospital stay in cases of early stage appendicitis was shorter for LA (1.9 ±0.31 days) as comared to OA (2.8 ±0.57 days), p value =0.000; while in complicated cases it was same in both groups (04 days, p =0.28). Analgesia requirement was low for LA, both for ES (p =0.05) and CA (p =0.01). Parents' satisfaction score was significantly higher for LA than OA. Conclusion: Laparoscopic appendectomy is a safe method and a substitute for open appendectomy among children. It should be preferred over open appen- dectomy even in cases of complicated appendicitis.